A Retrospective study to Analyze the Outcomes of Paediatric Pyeloplasty in Poorly Functioning Kidneys - Timbadiya, Nayan; S, Praveena; Matippa, Prasanna (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Pyeloplasty has success rate of up to 98%. We believe that paediatric pyeloplasty even in poorly functioning kidney, will result in maximum salvage of renal function. The aim of our study was to evaluate the outcome of pyeloplasty in poorly functioning kidneys with PUJO in the paediatric population. Methods: The children with PUJO with a GFR < 30 ml / min or < 30% differential function on DTPA, who underwent pyeloplasty in NU hospitals, Bengaluru over a period of 11 years 2 months, were included in our retrospective study. Anteroposterior diameters (APD) and parenchymal thickness (PT) were assessed at three months. After one year of surgery, they underwent DTPA. Outcomes analyzed were febrile UTI, the need for secondary procedures, structural and functional outcomes in operated kidneys till one year of follow-up. Results: A total of 30 patients with a mean age of four years ± 4 SD (standard deviation) with poor function on DTPA renogram (< 30%) were included in the study. 10 patients (33.33%) had a differential renal function (DRF) of 15% or less. Pre - operative mean PT was 4.7mm, mean APD was 38.5 mm, mean DRF was 19.3% and mean GFR was 17.7 ml / min. PT was increased to 6.4mm (± 2.4SD) and APD reduced to a 16.7 mm (± 10 SD) at the end of three months (p < 0.001). Increment in DRF percentage was 33.2 (± 9.4 SD) and GFR was 33.9 (± 12.5 SD) at the end of one year (p < 0.001). 13.3% of the patients had UTI, none of the study subjects required re-intervention within one year. Conclusions: The pyeloplasty for pediatric PUJO significantly improved the functional outcomes even in poorly functioning kidney, hence we recommend the pyeloplasty for selected pediatric cases of poorly functioning kidney with PUJO.